Covid-19 Pandemic and the Green Open Space Concept of Balinese Traditional Community - Waisnawa, I Made Jayadi (Bali Membangun Bali: Jurnal Bappeda Litbang, 2021)
Purpose: The purpose of this research was to determine the relationship between the concept of Green Open Space (Ruang Terbuka Hijau/RTH) of traditional Balinese society and the Covid-19 disease. Methodology: The method used in this research is a literature study which will be presented qualitatively. Results and duscussion: The meaning of the Green Open Space in the concept of hulu-teben, tri mandala, karang embang, sanga mandala, natah, karang tuang, kahyangan tiga and setra is an effort to minimize interactions that threaten the harmony of nature. Implication: The dominant spread of the virus in closed spaces can also be minimized through the concept of structuring the Green Open Space, both on a residential and public scale.